The endocannabinoid system: Overview of an emerging multi-faceted therapeutic target. (January 2019) - Chanda, Dipanjan; Neumann, Dietbert; Glatz, Jan F.C.
Highlights: The endocannabinoids anandamide (AEA) and 2-arachidonoylglyerol (2-AG) are endogenous lipid mediators with a short life span that exert paracrine or autocrine signaling. The endocannabinoid system is a ubiquitous cell signaling system that serves various protective roles in pathophysiological conditions. Modulation of the endocannabinoid system may be an effective approach to alter cellular metabolism. Abstract: The endocannabinoids anandamide (AEA) and 2-arachidonoylglyerol (2-AG) are endogenous lipid mediators that exert protective roles in pathophysiological conditions, including cardiovascular diseases. In this brief review, we provide a conceptual framework linking endocannabinoid signaling to the control of the cellular and molecular hallmarks, and categorize the key components of endocannabinoid signaling that may serve as targets for novel therapeutics. The emerging picture not only reinforces endocannabinoids as potent regulators of cellular metabolism but also reveals that endocannabinoid signaling is mechanistically more complex and diverse than originally thought.